Forecasting macroeconomic risks - Patrick A. Adams; Tobias Adrian; Nina Boyarchenko; Domenico Giannone (Federal Reserve Bank of New York, 2020)
We construct risks around consensus forecasts of real GDP growth, unemployment, and inflation. We find that risks are time-varying, asymmetric, and partly predictable. Tight financial conditions forecast downside growth risk, upside unemployment risk, and increased uncertainty around the inflation forecast. Growth vulnerability arises as the conditional mean and conditional variance of GDP growth are negatively correlated: downside risks are driven by lower mean and higher variance when financial conditions tighten. Similarly, employment vulnerability arises as the conditional mean and conditional variance of unemployment are positively correlated, with tighter financial conditions corresponding to higher forecasted unemployment and higher variance around the consensus forecast.
Keywords: C22; E17; E37; 330; macroeconomic uncertainty; quantile regressions; financial conditions